2019
DOI: 10.1097/fch.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Body Mass Index and Body Image Disturbances Among South African Mothers and Their Daughters Living in Soweto, Johannesburg

Abstract: In South African families, a phenomenon of mothers' acceptance of stoutness coexists with their daughters' appreciation for thinness. A sample of N = 615 mother-and-daughter pairs was recruited to conjointly identify the relationships toward body image and body mass index between both groups by assessing body weight satisfaction, body esteem, and eating disorders risk. We observed higher prevalence of obesity in mothers and higher eating disorders risk in daughters, while mother-daughter relationships were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 70 publications
0
23
0
1
Order By: Relevance
“…4). We observed a positive relationship between age category and ideal body size, with valorisation of underweight in some adolescent females (63,85) and valorisation of overweight in middle-aged women (27,73,77,78,86,97) . The rural-urban comparison showed that the ideal BMI category was higher in rural than urban areas in South Africa (27,69) , Senegal (93,116) and Cameroon (114) .…”
Section: Data Synthesismentioning
confidence: 66%
See 1 more Smart Citation
“…4). We observed a positive relationship between age category and ideal body size, with valorisation of underweight in some adolescent females (63,85) and valorisation of overweight in middle-aged women (27,73,77,78,86,97) . The rural-urban comparison showed that the ideal BMI category was higher in rural than urban areas in South Africa (27,69) , Senegal (93,116) and Cameroon (114) .…”
Section: Data Synthesismentioning
confidence: 66%
“…Using body image scales, one study (51) found that 34•6 % of Kenyan women living in urban Nairobi underestimated their body weight; with 28•8 % of women who underestimated their weight classified as obese, a pattern also observed in Cameroonian urban women (42) . The same was also observed with overweight/obesity in Nigerian students and South African black urban women, as well as in black schoolgirls, Algerian Saharawi refugees, urban (80) Mauritius High Urban/Rural Females Adolescents 13-18 90 Ettarh et al (51) Kenya Medium Urban slums Females Adults 42•0 (no SD) Jafri et al (81) Morocco Medium Urban Females All ≥ 18 425 El Ansari et al (82) Egypt Medium Urban Females Adolescents 18•6 (1•2) Gitau et al (85) South Africa Medium Urban Mixed Adolescents 13 and 17 1302 (♀: 675; ♂: 627) Gitau et al (83) South Africa Medium Urban Females Adolescents 15•0 (no SD) 183 Gitau et al (84) South Tunisian, Moroccan and Malawian women (24,53,79,87,90,96,97,115) . Only 37•1 % of Ghanaian women living in Accra perceived their current body size as overweight or obese, even though 49•9 % were in these weight categories (70) , a pattern also observed by others in the same city (48,78) .…”
Section: Data Synthesismentioning
confidence: 99%
“…The maternal lifestyle, especially eating behaviors, choice of foods, and dietary intake, can expose her offspring to obesity [20]. Moreover, maternal normalization and valorization of obesity, already identified in several African studies [23,37], can make overweight and obesity the body norm at home for children, as observed in a recent South African study [17]. Thus, adolescents living in urban-poor Soweto could be exposed to two distinct body norm models, with the household environment and cultural values potentially promoting stoutness and the adolescent peer network reinforced by media images and messages promoting thinness, as discussed in a recent South African study [23].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Zaccagni et al [30] developed a new tool (the FAI index) that assesses the perceived weight status, analyzing the figure chosen as their actual and BMI in a sample of undergraduate students. More recently, Cohen et al [31] proposed an index (body weight self-satisfaction index) similar to the previous one on the basis of another Figure Rating Scale. For the present study, we decided to evaluate in a large sample of young adults the consistency of the body figure perceived as actual with the fat status objectively assessed by bioimpedance analysis (BIA).…”
Section: Introductionmentioning
confidence: 99%